Diagnosis of Tuberculous Lymphadenitis from Fine Needle Aspirate by PCR (Bangladesh Journal of Medical Microbiology, 2017)
Lymph node involvement is the commonest form of extra pulmonary tuberculosis (EPTB). This study was undertaken to evaluate the role of PCR using IS6110 as a target for Mycobacterium tuberculosis complex in the diagnosis of tuberculous lymphadenitis (TB-L) and was done in Microbiology department of Sir Salimullah Medical College from July 2009 to June 2010. Fine needle aspiration was performed on 107 patients with a clinical suspicion of tuberculous lymphadenitis from different hospitals of Dhaka City Corporation area. All the aspirated samples were subjected to culture and PCR for M.tuberculosis. Out of 107 patients with lymphadenopathy most of the patients (85.9%) had cervical lymph node enlargement followed by axillary groups (12.1%) and inguinal groups (1.9%). Out of 107 cases, 65 (60.7%) were PCR positive and 56 (52.3%) were culture positive. Among 51 (47.7%) culture negative cases 9 (17.65) were PCR positive. Sensitivity of PCR was 100% and specificity was 82.4%.The positive predictive value (PPV), negative predictive value (NPV) and accuracy of PCR were 86.2%, 100% and 91.6% respectively. PCR is the most sensitive in the detection of M.tuberculosis in fine needle aspirate and could be useful technique in establishing the diagnosis of tuberculous lymphadenitis.